Liquidity risk and maturity management over the credit cycle - Mian, Atif; Santos, João A.C. (Journal of Financial Economics, 2018)
We show that firm demand-side factors are strong drivers of procyclical refinancing behavior over the credit cycle using novel data from the Shared National Credit program. Firms are more likely to refinance early when credit conditions are good to keep the effective maturity of their loans long and hedge against having to refinance in tight credit conditions. High credit quality firms are better able to hedge, making their refinancing propensity more sensitive to credit cycles than less creditworthy firms. There is a strong relationship between refinancing a loan, and subsequent growth in capital expenditure, especially when a loan is refinanced early.